Die Deutsche Bundesbank in der Globalsteuerung: Zur Diskussion über die Instrumente und die Unabhängigkeit der Zentralbank in der Ära Schiller (1966-1972); The German Central Bank and Macro Regulation: On the Discussion of the Instruments and Independence of the Deutsche Bundesbank in the Era of Karl Schiller (1966-1972) - Christian Marx (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte (VSWG), 2024)
– Keynesian-inspired macro regulation gained importance in West German economic policy from the mid-1960s and was enshrined in law through the Stability and Growth Act in 1967. In the context of the legislative process, the question arose as to what extent the Deutsche Bundesbank should be given new central bank instruments in order to achieve the goal of price stability. In the end, their implementation was rejected as the government demanded participation rights that contradicted the principle of central bank independence. Based on documents from the Historical Archive of the Deutsche Bundesbank and the Federal Archives, the article examines the arguments in favor of the new instruments and the reasons that prevented their implementation.
Keywords: B22; B26; E51; E52; E58; N14; N24; N44; 330; monetary history; inflation; central bank; central bank independence